Hispanic migration and urban development studies from Washington DC - Pumar, Enrique S., 1956- (Bingley, U.K. : Emerald, 2012)
This volume of Research in Race and Ethnic Relations analyzes the pattern of assimilation and incorporation among the Hispanic population in the Washington DC metro region. Following a comprehensive introduction looking at theoretical and policy implication the book consists of two conceptual chapters discussing the literature of ethnic incorporation and assimilation in urban regions, one chapter analyzing demographic trends among the Hispanic population, and four chapters analyzing different issues related to assimilation, in particular the nature entrepreneurialship, civic engagement, political participation, and education among migrants. This book makes a considerable contribution to the literature of emerging gateways in the field of migration and urban development with articles from notable academics and public policy analysts in their respective fields. It is the only comprehensive study of its kind concerning Hispanic migration to the Washington DC region. (The majority of other studies in the field are based on data from major metropolitan cities such as New York, Chicago and Los Angeles).
Preface / Enrique S. Pumar -- Metropolitan Washington : a new immigrant gateway / Audrey Singer -- National development, capability, and the segmented assimilation of Hispanics in Washington, DC / Enrique S. Pumar -- New data, new horizons, and new measures : theoretical and applied outcomes related to the regional focus of research on ethnic populations / John Kromkowski -- A growing and diverse population : Latinos in the Washington, DC, metropolitan area / Mark Hugo Lopez, Daniel Dockterman -- Residential patterns and an overview of segregation and discrimination in the greater Washington, DC, metropolitan region / Judith Perez -- Hispanic entrepreneurship in a global city : the Bolivian diaspora in Washington, DC / Marie D. Price -- Latino organizations and immigrant integration in the Washington, DC, region / Carol J. De Vita, Erwin de Leon -- Strengthening and unifying Latino and African-American families : community psychology in Washington, DC / Sandra Barrueco, Eileen Twohy -- Immigration, Latinos, and crime : a ward-level exploratory assessment of Washington DC property and violent crime rates / Daniel E. Martínez -- Reflections on migration and urban development / Enrique S. Pumar, Patrick Stark.
Print version record
Keywords: Social Science -- Ethnic Studies -- Hispanic American Studies; Social Science -- Emigration & Immigration; Social Science -- Sociology -- General; Social interaction; Social groups; Hispanic Americans -- Migrations; Minorities -- Washington (D.C.); Race relations; Hispanic Americans -- Washington (D.C.)